Study on Fault Current of DFIG during Slight Fault Condition - Xiangping Kong; Zhe Zhang; Xianggen Yin; Zhenxing Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to ensure the safety of DFIG when severe fault happens, crowbar protection is adopted. But during slight fault condition, the crowbar protection will not trip, and the DFIG is still excited by AC-DC-AC converter. In this condition, operation characteristics of the converter have large influence on the fault current characteristics of DFIG. By theoretical analysis and digital simulation, the fault current characteristics of DFIG during slight voltage dips are studied. And the influence of controller parameters of converter on the fault current characteristics is analyzed emphatically. It builds a basis for the construction of relay protection which is suitable for the power gird with accession of DFIG. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2542